Alpha‐synuclein gene duplication: Marked intrafamilial variability in two novel pedigrees. Issue 6 (6th June 2013) - Elia, Antonio E.; Petrucci, Simona; Fasano, Alfonso; Guidi, Marco; Valbonesi, Stefano; Bernardini, Laura; Consoli, Federica; Ferraris, Alessandro; Albanese, Alberto; Valente, Enza Maria
ABSTRACT Background Multiplications of the SNCA gene that encodes alpha‐synuclein are a rare cause of autosomal dominant Parkinson's disease (PD). Methods Here, we describe 2 novel families in which there is autosomal dominant PD associated with SNCA duplication, and we compare the clinical features of all known patients carrying 3 or 4 SNCA copies. Results Affected members in family A presented with early onset PD that was variably associated with nonmotor features, such as dysautonomia, cognitive deficits, and psychiatric disturbances. In family B, the clinical presentation ranged from early onset PD‐dementia with psychiatric disturbances to late onset PD with mild cognitive impairment. Conclusions The presence of 4 SNCA copies is associated with a rich phenotype, characterized by earlier onset of motor and nonmotor features compared with patients who bear 3 SNCA copies. The clinical spectrum associated with SNCA duplications is wide, even within a single family, suggesting a role for as yet unidentified genetic or environmental modifiers. © 2013 Movement Disorder Society